SOX9, through Interaction with Microphthalmia-associated Transcription Factor (MITF) and OTX2, Regulates BEST1 Expression in the Retinal Pigment Epithelium - Masuda, Tomohiro (American Society for Biochemistry and Molecular Biology, 2010)
BEST1 is highly and preferentially expressed in the retinal pigment epithelium (RPE) and causes Best macular dystrophy when mutated. We previously demonstrated that the human BEST1 upstream region −154 to +38 bp is sufficient to direct expression in the RPE of transgenic mice, and microphthalmia-associated transcription factor (MITF) and OTX2 regulate this BEST1 promoter. However, a number of questions remained. Here, we show that yeast one-hybrid screen with bait corresponding to BEST1 −120 to −88 bp identified the SOX-E factors, SOX8, SOX9, and SOX10. A paired SOX site was found in this bait, and mutation of either of the paired sites significantly decreased BEST1 promoter activity in RPE primary cultures. Among the SOX-E genes, SOX9 is highly and preferentially expressed in the RPE, and chromatin immunoprecipitation with fresh RPE cells revealed binding of SOX9, but not SOX10, to the BEST1 region where the paired SOX site is located. BEST1 promoter activity was increased by SOX9 overexpression and decreased by siRNA-mediated SOX9 knockdown. Importantly, SOX9 physically interacted with MITF and OTX2 and orchestrated synergistic activation of the BEST1 promoter with the paired SOX site playing essential roles. A combination of the expression patterns of SOX9, MITF, and OTX2 yielded tissue distribution remarkably similar to that of BEST1. Lastly, the BEST1 promoter was also active in Sertoli cells of the testis in transgenic mice where SOX9 is highly expressed. These results define SOX9 as a key regulator of BEST1 expression and demonstrate for the first time its functional role in the RPE.